Ustekinumab serum concentrations are associated with clinical outcomes in Crohn’s disease: a regional multi-center pilot study - Thomann, Anne K.; Schulte, Lucas-Alexander; Globig, Anna-Maria; Hoffmann, Peter; Klag, Thomas-Matthias; Itzel, Timo; Teufel, Andreas; Schreiner, Rupert; Scheffe, Nina; Ebert, Matthias; Wehkamp, Jan; Gauss, Annika; et al. (Zeitschrift für Gastroenterologie, 2020)
Background and aim The role of therapeutic drug monitoring (TDM) in ustekinumab (UST) therapy for Crohn’s disease (CD) has not been established, as only few studies have analyzed the relationship between UST serum concentrations and clinical outcome. In this pilot study, we retrospectively examined the potential of UST-concentrations (cUST) 8 weeks after induction (cUSTw8) to predict clinical response at week 16. Methods Serum samples and clinical data from patients (n = 72) with moderate to severely active CD who received intravenous induction with UST were retrospectively analyzed. cUST were quantitated using liquid chromatography-tandem mass spectrometry (LC-MSMS). A receiver-operating characteristic (ROC) curve and area under ROC curve (AUROC) was computed to analyze the predictive potential of cUSTw8 for clinical response at week 16 and to determine the minimal therapeutic UST trough concentration. Results Forty-four patients (61 %) achieved clinical response to UST therapy at week 16. cUSTw8 was moderately effective to predict clinical response with a minimal therapeutic cUSTw8 of 2.0 mg/l (AUC 0.72, p = 0.001). Conclusion Trough concentrations of UST 8 weeks after induction predict clinical response to therapy in week 16 with moderate sensitivity and specificity. TDM using LC-MSMS could prove beneficial in personalized UST therapy of patients with CD by identifying individuals with subtherapeutic concentrations who might benefit from dose escalation.